Intensitas Nyeri Persalinan Kala I Fase Laten pada Ibu Inpartu menggunakan Birth Ball Exercise - Putu Indah Sintya Dewi; Kadek Yudi Aryawan; Putu Agus Ariana; Ni Ayu Putu Eka Nandarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to analyze the effect of birth ball exercise on the intensity of labor in the first stage of latent phase in mothers of mothers in BPM